O reconhecimento do stalking no Brasil : em busca de maior proteção da pessoa vulnerável - Silva, Bruno Martins da Costa (2016)
Stalking is not a type of conduct in itself, but a complex modus operandi that can be composed by several conducts, included the licit and mundane ones. Motives and objectives can vary. Victims and stalkers include several profiles, enabling multiple dynamics. Begining in 1990’s, stalking is subject of debate, research and legislation in Common Law legal systems. In 1998, Belgium enacted the first anti-stalking law among Civil Law legal systems. Currently, most European countries have anti-stalking laws. In Brazil, there is no data, research or public debate about the subject. Still, stalking was included as a crime in the latest draft of the new Penal Code. The dissertation’s objectives are: defining stalking; presenting how different legal systems deal with the problem; discussing positive and negative aspects of different normative models; and, analyzing the Brazilian Legal System in order to understand: (i) if Brazil needs an anti-stalking law; (ii) which normative model is most suitable to Brazil’s Legal System. The applied method is the hypothetico-deductive. Research started over a central hypothesis: a balanced anti-stalking law needs civil provisions that rule stalking conducts that are between mundane acts and criminal behavior. Research showed that normative models’ evolution tend to result in the use or enactment of civil provisions to grant efficiency to anti-stalking laws. In conclusion, it seems that Brazil does not need an antistalking law. In Brazil, tort system is flexible; civil procedures are strong; and criminal law offers several options to neutralize stalking cases. Thus, the normative model could be easily constructed within the current Legal System, without criminalize such a complex phenomenon.